Modulation of the Naked‐Eye and Fluorescence Color of a Protonated Boron‐Doped Thiazolothiazole by Anion‐Dependent Hydrogen Bonding. Issue 49 (13th July 2022) - Hagspiel, Stephan; Fantuzzi, Felipe; Arrowsmith, Merle; Gärtner, Annalena; Fest, Maximilian; Weiser, Jonas; Engels, Bernd; Helten, Holger; Braunschweig, Holger
Abstract: The reaction of a cyclic alkyl(amino)carbene (CAAC)‐stabilized thiazaborolo[5, 4‐ d ]thiazaborole (TzbTzb) with strong Brønsted acids, such as HCl, HOTf (Tf=O2 SCF3 ) and [H(OEt2 )2 ][BAr F 4 ] (Ar F =3, 5‐(CF3 )2 C6 H3 ), results in the protonation of both TzbTzb nitrogen atoms. In each case X‐ray crystallographic data show coordination of the counteranions (Cl −, OTf −, BAr F 4 − ) or solvent molecules (OEt2 ) to the doubly protonated fused heterocycle via hydrogen‐bonding interactions, the strength of which strongly influences the 1 H NMR shift of the N H protons, enabling tuning of both the visible (yellow to red) and fluorescence (green to red) colors of these salts. DFT calculations reveal that the hydrogen bonding of the counteranion or solvent to the protonated nitrogen centers affects the intramolecular TzbTzb‐to‐CAAC charge transfer character involved in the S0 →S1 transition, ultimately enabling fine‐tuning of their absorption and emission spectral features. Abstract : The visible and fluorescence colors of a doubly protonated boron‐doped thiazolothiazole can be modulated by tuning its hydrogen‐bonding interactions with its counteranions or donor solvent molecules (Cl −, O3 SCF3 −, B(3, 5‐(CF3 )2 C6 H3 )4 −, OEt2 ). DFT calculations show that these affect the relative energies of the π orbitals involved in the S0 →S1 transition, thus enabling fine‐tuning of their absorption and emission spectral features.